Before the Revolution (Israel, Iran), 2013, Color, 60 min. In Hebrew and Persian with English subtitles. Director: Dan Shadur. Producer: Barak Heymann. Distributor: Heymann Brothers Films; 2 Barzilay Street, Tel Aviv, 65113, Israel; +972-3-5602701; info@heymannfilms.com. Issue 2 (August 2015) - Miller, Corey
Abstract : Director Dan Shadur's parents, Avi and Nili, were part of a multitude of Israeli diplomats and businesspeople doing business in Iran before the Islamic Revolution of 1979. For many of these people, their years in Iran were the happiest moments of their lives. They enjoyed big apartments, substantial earning power, vacations in the mountains, royal dinners, and front-row seating at military parades. Of course, all of this was to disappear starting with the tumultuous period at the end of 1978.